USES OF GEOGRAPHIC CONCEPT TERRITORY AND ITS RELEVANCE IN THE ANALYSIS OF TERRITORIAL AND ENVIRONMENTAL CONFLICTS IN THE AMAZON - Gomes e Silva, Ivana de Oliveira [UNESP]; Silva, Paulo Lucas da (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2016)
The territory concept, generated from the concept of space, designates spatialized power relations. Limits are set, broken and reshaped according to the successive power of shares issued in a given space-time. The ongoing territorial rearrangements in the Amazon, previously generated by the Portuguese Crown, Empire and now, with the advent Republican, by the capitalist state, imply conflicts and losses for the working class. The recent process called neo-developmentism updates cyclical desterreacao practices to subjugate the working class displacing the previously conquered territories and demobilizing it for triggering various strategies ranging from co-opting the criminalization of their resistance movements. In researched crop in the context of construction of the Belo Monte hydroelectric plant in southwestern Para, we study the dialectical movement of adaptation and resistance undertaken by social movements before the imposition of energy policies implemented by the PT government of Luiz Inacio Lula da Silva and Dilma Rousseff. Investigates forms of protest triggered by the working class in a troubled political moment.
Keywords: Territory; workers; Capitalist state; Amazon; neo-developmentism